Analisis metafora konseptual dalam puisi Indonesia dan Korea karya Chairil Anwar dan Seo Jeong-ju - Trisiana, Dinda; Ansas, Velayeti Nurfitriana; Lubis, Arif Husein (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2024)
Poetry is a literary work that is intrinsically linked to the use of metaphor. This study examines the conceptual metaphors found in Indonesian poetry by Chairil Anwar and Korean poetry by Seo Jeong-Ju. Specifically, the research aims to identify the forms of conceptual metaphors present in the poetry of these two poets, using a contrastive analysis approach based on Johnson and Lakoff's theory of conceptual metaphor. The method employed is a qualitative descriptive method, utilizing note-taking data collection techniques. The data consists of 10 poems by Chairil Anwar and 10 poems by Seo Jeong-Ju (서정주). The findings reveal similarities in the use of conceptual metaphors, with both poets predominantly employing structural metaphors and using orientational metaphors the least. However, there are quantitative differences; Chairil Anwar's poetry contains a greater number of metaphors compared to that of Seo Jeong-Ju. Therefore, this research not only provides insight into the use of metaphors in Korean and Indonesian poetry but also serves as a valuable reference for further literary research, particularly in the study of poetry and metaphor.